Indonesia's Bioethanol Industry Diamond Porter Model - Gita K. Indahsari; Arief Daryanto; Endang Gumbira Said; Rudi Wibowo (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2011)
-